THE IMPACT OF SOCIAL MEDIA USAGE TOWARDS STUDENTS' BEHAVIOR AND ACHIEVEMENT IN LEARNING PROCESS - Siti Nurhidayah Al-Anshari; Uziah Annasa'i Munthe (Universitas Pendidikan Indonesia, 2022)
This research is based on the background that there are still students who need help understanding the use of social media well, so that it impacts student learning behavior at school. This affects student learning outcomes in schools that could be more satisfactory because social media is not used for learning but is more used as a place of entertainment. Based on this, this study will reveal how the influence of the use of social media on the behavior and achievement of students in learning activities. The methodology used in this study is a qualitative approach with a qualitative descriptive method. The data collection technique was carried out by interviewing by question and answer, while face to face with the resource person. The results of this study can be concluded that using social media in learning activities has a positive and negative impact on student behavior and achievement. The positive effect can add insight, while the negative impact is when in learning activities students secretly open social media other than for learning activities. Based on the results of this study, social media does not entirely negatively affect student behavior and achievement at school. However, due to the COVID-19 pandemic, social media has become a means to assist learning activities between teachers and students during online learning.